Eksistensi Teks Geguritan Jayaprana Sebagai Representasi Aksiologi Religius Dan Sosiobudaya Masyarakat Hindu Bali - I Made Luwih (Jayapangus Press, 2026)
Geguritan Jayaprana is a classical Balinese literary work that embodies the philosophical, religious, and sociocultural values of Balinese Hindu society. However, studies that integratively examine this work from an axiological perspective by connecting its ethical, aesthetic, religious, and sociocultural dimensions remain limited. This study aims to analyze the existence of Geguritan Jayaprana as a representation of axiological, religious, and sociocultural values that shape the worldview of Balinese Hindu society. This study employed a qualitative approach with a descriptive-analytical design based on library research. The primary data were derived from Ketut Ginarsa’s 1978 text of Geguritan Jayaprana and analyzed using content analysis, a hermeneutic approach, and an axiological perspective. The findings reveal that the ethical dimension is manifested through the values of satya, bhakti, loyalty, responsibility, and sacrifice, as reflected in Jayaprana’s character. The aesthetic dimension is evident in the portrayal of tragedy, narrative structure, symbolism, and the use of Pupuh Ginada, which intensifies the emotional atmosphere. The religious dimension is represented through the teachings of Karma Phala, Punarbhawa, Dharma, and the harmony between Bhuana Agung and Bhuana Alit. Meanwhile, the sociocultural dimension reflects feudal social structures, collectivist culture, etiquette, loyalty, and criticism of the abuse of power. The interconnection among these dimensions demonstrates that individual, spiritual, and social values are integrated as guidelines for establishing harmonious relationships among human beings, society, nature, and God in contemporary Balinese Hindu life. The findings indicate that Geguritan Jayaprana functions not merely as entertainment but also as a medium for moral education, character development, religious teaching transmission, and cultural identity preservation. This study concludes that Geguritan Jayaprana is a relevant source of cultural literacy for revitalizing local values, strengthening ethical and religious awareness, and responding to social changes and the challenges of globalization.